2022
DOI: 10.1002/slct.202201082
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Hydrophosphorylation of Dibenzo[b,f][1,4]oxa‐/thiazepines by Acid Catalysis

Abstract: A protocol for the acid-catalyzed synthesis of phosphorylated dihydrodibenzoxa-/thiazepine derivatives from dibenzo[b,f][1,4]oxa-/thiazepines has been established. The reaction appears compatible with a range of functional groups in both the dibenzo[b,f][1,4]oxa-/thiazepine, H-phosphonate and especially diarylphosphine oxide phosphorylation partners, affording moderate to excellent yields of the corresponding products. The present method further expands the utility of Pudovik reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In 2022, Wang and co‐workers found that hydrophosphorylation of tri‐cyclic seven‐membered imines 1 , 11 can be catalyzed by a Lewis acid, or a Brønsted acid as a catalyst (Scheme 13). [37] The reaction of dibenzo[ b , f ][1,4]oxazepines 1 with diarylphosphine oxides 34 , or H‐phosphites was performed in the presence of La(OTf) 3 as a Lewis acid catalyst. While pentafluorobenzoic acid (PFBA) as a Brønsted acid was selected as the best catalyst for the coupling reaction between dibenzo[ b , f ][1,4]thiazepines 11 with phosphorylating reagents 34 .…”
Section: Functionalization Of Tri‐cyclic Seven‐membered Imines/aminesmentioning
confidence: 99%
“…In 2022, Wang and co‐workers found that hydrophosphorylation of tri‐cyclic seven‐membered imines 1 , 11 can be catalyzed by a Lewis acid, or a Brønsted acid as a catalyst (Scheme 13). [37] The reaction of dibenzo[ b , f ][1,4]oxazepines 1 with diarylphosphine oxides 34 , or H‐phosphites was performed in the presence of La(OTf) 3 as a Lewis acid catalyst. While pentafluorobenzoic acid (PFBA) as a Brønsted acid was selected as the best catalyst for the coupling reaction between dibenzo[ b , f ][1,4]thiazepines 11 with phosphorylating reagents 34 .…”
Section: Functionalization Of Tri‐cyclic Seven‐membered Imines/aminesmentioning
confidence: 99%
“…Figure S10. P(O),NH-acetals, obtained by reactions of dibenzo[b,f][1,4]-oxa-and -thi-azepines with SPOs [193]. …”
mentioning
confidence: 99%